The Effect of Antioxidants on the Properties of Red Blood Cells From Patients With Sickle Cell Anemia - Al Balushi, Halima; Hannemann, Anke; Rees, David; Brewin, John; Gibson, John Stanley (Frontiers in Physiology, 2019)
Oxidative damage to red blood cells (RBCs) may contribute to pathogenesis of sickle cell anaemia. Reducing the deleterious effects of oxidants by exposing RBCs to a number of antioxidants has been shown to have protective effects against lipid and protein peroxidation. We hypothesise that antioxidants may also have beneficial effects on the abnormal membrane permeability of sickle cells. Increased cation permeability of these cells encourages HbS polymerisation by causing RBC dehydration and also leads to externalisation of the prothrombotic aminophospholipid phosphatidylserine (PS). Three antioxidants with different mechanisms of action were investigated – dithiothreitol, N-acetylcysteine and quercetin. All three were found to inhibit the main cation pathways responsible for dehydration – the deoxygenation-induced cation conductance (or Psickle), the Ca2+-activated K+ channel (or Gardos channel) and the K+-Cl- cotransporter. They also reduced Ca2+-induced PS exposure and haemolysis. Findings provide evidence for additional beneficial actions of antioxidants in maintenance of rheology and reducing vascular adhesion, and further inform the rationale for their clinical use.